Specific alterations of regional myocardial work in strength-trained athletes using anabolic androgenic steroids compared to athletes with genetic hypertrophic cardiomyopathy - Antoine Grandperrin; Frédéric Schnell; Erwan Donal; Elena Galli; Christophe Hedon; Olivier Cazorla; Stéphane Nottin (Elsevier, 2023)
Background: Strength-trained athletes using anabolic androgenic steroids (AAS) have left ventricular (LV) hypertrophy and myocardial fibrosis that can lead to sudden cardiac death. A similar feature was described in athletes with hypertrophic cardiomyopathy (HCM), which complicates the diagnosis for clinicians. In this context, we aimed to compare the LV function of the 2 populations by measuring global and regional strain and myocardial work using speckle-tracking imaging. Methods: Twenty-four strength-trained asymptomatic athletes using AAS (AAS-Athletes), 22 athletes diagnosed with HCM (HCM-Athletes), and 20 healthy control athletes (Ctrl-Athletes) underwent a resting echocardiography to assess LV function. We evaluated LV global and regional strains and myocardial work, with an evaluation of the constructive work (CW), wasted work, and work efficiency (WE). Results: Compared to Ctrl-Athletes, both AAS-Athletes and HCM-Athletes had a thicker interventricular septum, with majored values in HCM-Athletes. LV strain was reduced in AAS-Athletes and even more in HCM-Athletes. Consequently, global WE was significantly diminished in both AAS and HCM-Athletes (93% ± 2% in Ctrl-Athletes, 90% ± 4% in AAS-Athletes, and 90% ± 5% in HCM-Athletes (mean ± SD); p < 0.05). Constructive work and WE regional analysis showed specific alterations, with the basal septal segments preferentially affected in AAS-Athletes, and both septal and apical segments affected in HCM-Athletes. Conclusion: The regional evaluation of myocardial work reported specific alterations of the major LV hypertrophy induced by the regular use of AAS compared to the LV hypertrophy due to HCM. This finding could help clinicians to differentiate between these 2 forms of pathological hypertrophy.